2021
DOI: 10.1039/d0ob00413h
|View full text |Cite
|
Sign up to set email alerts
|

DDQ/FeCl3-mediated tandem oxidative carbon–carbon bond formation for the Synthesis of indole–fluorene hybrid molecules

Abstract: A series of diverse and complex hybrid structures of indole bearing fluorene were obtained in the presence of DDQ and FeCl3 with high regioselectivity under mild conditions from biaryl tethered 3-(methylene)indoline in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…However, based on our previous studies along with our present results of investigations, for the oxidation of the C-3 benzylidine indolines 2a , the generation of an allylic carbocation at the C-2 position in 2a followed by isomerization to produce the 3-indolyl carbocation is more facile compared to the direct formation of a diaryl carbocation at the C-3 position of indole in 2a′ due to aromatic stabilization. The energy of the intermediates was calculated through a density functional theory (DFT) study, and the reaction thermos-energy profile is shown in Figure .…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…However, based on our previous studies along with our present results of investigations, for the oxidation of the C-3 benzylidine indolines 2a , the generation of an allylic carbocation at the C-2 position in 2a followed by isomerization to produce the 3-indolyl carbocation is more facile compared to the direct formation of a diaryl carbocation at the C-3 position of indole in 2a′ due to aromatic stabilization. The energy of the intermediates was calculated through a density functional theory (DFT) study, and the reaction thermos-energy profile is shown in Figure .…”
Section: Resultssupporting
confidence: 53%
“…Therefore, a mild and efficient method to access 3-acyl indoles is highly desired. With our continuous efforts after victorious developments of oxidative C–C/C–N bond-forming strategies, we envisaged that dehydrogenation at the α-sp 3 C–H bond of the arylsulfonamide moiety at the C-2 carbon in C-3-alkyl-/arylidine indolines could introduce oxidative hydroxylation or oxo-functionalization at the C-3 position via oxidative isomerization/aromatization to afford 3-acyl indoles. In this regard, a catalytic combination of DDQ and a nitrate source in the presence of molecular oxygen was anticipated as the most efficient oxidant .…”
Section: Introductionmentioning
confidence: 99%
“…Kar and co-workers demonstrated this (Scheme 25) in the conversion of indolene 121 to cationic indole derivative 122 . 80 An intramolecular Friedel–Crafts alkylation reaction provided fluorene-substituted indole 123 . Notably the isomeric substrate in which the indole nucleus is intact reacted far less efficiently, demonstrating the importance of starting material energy on oxidation rates.…”
Section: Quinone Oxidantsmentioning
confidence: 99%
“…This pathway offers high functional group tolerance as shown in Scheme 19. 44 During oxidative C-C bond-forming reactions, the control of cyclization and polymer formation is quite tricky. DDQ has provided solution to these challenging problems by controlling the cyclization during C-C bond formation and suppressing the process of polymerization.…”
Section: Scheme 18 Synthesis Of Rubicene Derivatives Under Scholl's Reaction Conditionsmentioning
confidence: 99%